PENERAPAN MODEL PEMBELAJARAN PETA PIKIRAN UNTUK MENINGKATKAN KEMAMPUAN MENULIS CERPEN ANAK BERBASIS KARAKTER MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIMED - Mursini . (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2012)
The research was motivated by the success of the Children's Literaturecourse. During this time students taking courses in children's literature lessinterested in writing children's stories, because they think children's literature isnot interesting. The use of a less appropriate learning model is very influential inteaching and learning smooth and therefore can not meet the Unimed passingstandards  specified in Children's Literature Lecture Events Unit. Lecturers whoteach the exact learning model is expected to improve the ability of students to writea short story based on the character of the child. Many models can be applied in thelearning process, one of which is a model of learning Mind Map. Learning isproving an increase in the ability of students to write a short story based on thecharacter of the child's learning model implemented Mind Maps. Analysis of thedata used is descriptive analysis that describes the direction of change, improvementchanges, and understanding of concepts. The results of this study began beforeimplementing the learning cycle that initial test results with an average value of69.3. After the first cycle of the pretest is then performed by applying learningmodels with Mind Maps average value of 84.7. These results are considered to beless satisfactory then continue the cycle II conducted by applying the  model oflearning  Mind Map  with the average value of 91.8 were categorized as verycompetent. Furthermore concluded that the model of learning Mind Map canenhance the ability to write short stories character based child student in theDepartment of Indonesian.